The influence of biotic and abiotic factors on the bacterial microbiome of gentoo penguins ( Pygoscelis papua ) in their natural environment - Kaczvinsky, C; Levy, H; Preston, S; Youngflesh, C; Clucas, G; Lynch, HJ; Hart, T; Smith, AL (Nature Research, 2024)
The microbiome is a key factor in the health, well-being, and success of vertebrates, contributing to the adaptive capacity of the host. However, the impact of geographic and biotic factors that may affect the microbiome of wild birds in polar environments is not well defined. To address this, we determined the bacterial 16S rRNA gene sequence profiles in faecal samples from pygoscelid penguin populations in the Scotia Arc, focusing on gentoo penguins. This mesopredatory group breeds in defined colonies across a wide geographic range. Since diet could influence microbiome structure, we extracted dietary profiles from a eukaryotic 18S rRNA gene sequence profile. The bacterial microbiome profiles were considered in the context of a diverse set of environmental and ecological measures. Integrating wide geographic sampling with bacterial 16S and eukaryotic 18S rRNA gene sequencing of over 350 faecal samples identified associations between the microbiome profile and a suite of geographic and ecological factors. Microbiome profiles differed according to host species, colony identity, distance between colonies, and diet. Interestingly there was also a relationship between the proportion of host DNA (in relation to total 18S rRNA gene signal) and the microbiome, which may reflect gut passage time. Colony identity provided the strongest association with differences in microbiome profiles indicating that local factors play a key role in the microbiome structure of these polar seabirds. This may reflect the influence of local transfer of microbes either via faecal-oral routes, during chick feeding or other close contact events. Other factors including diet and host species also associate with variation in microbiome profile, and in at least some locations, the microbiome composition varies considerably between individuals. Given the variation in penguin microbiomes associated with diverse factors there is potential for disruption of microbiome associations at a local scale that could influence host health, productivity, and immunological competence. The microbiome represents a sensitive indicator of changing conditions, and the implications of any changes need to be considered in the wider context of environmental change and other stressors.